2019
DOI: 10.1002/jso.25518
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of arterial ischemia or venous occlusion on vascularized groin lymph nodes in a rat model

Abstract: BackgroundReported ischemia time of vascularized lymph nodes was 5 hours. This study investigated the effects of arterial ischemia and venous occlusion on vascularized lymph node function in rats.MethodsBilateral pedicled groin lymph node flaps were raised in 27 Lewis rats. Femoral artery and vein were separated and clamped for 1, 3, 4, or 5 hour(s). Lymph node flap perfusion and drainage were assessed by laser Doppler flowmetry and indocyanine green lymphography. Histologic changes were assessed using hematox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 32 publications
0
17
1
Order By: Relevance
“…Moreover, lymph nodes undergoing 120 minutes ischemia also contained markedly higher numbers of proliferating PCNA + and apoptotic Casp-3 + cells as well as CD68 + macrophages and MPO + neutrophilic granulocytes when compared to lymph nodes of the IR-45 and control group. In contrast to our findings, the current opinion on critical ischemia time of VLN flaps is four hours as evaluated for inguinal VLN flaps in a rat model [28,29]. However, a recent analysis of inflammatory biomarkers revealed that significant IR injury can occur with as little as two hours of ischemia [30].…”
Section: Plos Onecontrasting
confidence: 99%
“…Moreover, lymph nodes undergoing 120 minutes ischemia also contained markedly higher numbers of proliferating PCNA + and apoptotic Casp-3 + cells as well as CD68 + macrophages and MPO + neutrophilic granulocytes when compared to lymph nodes of the IR-45 and control group. In contrast to our findings, the current opinion on critical ischemia time of VLN flaps is four hours as evaluated for inguinal VLN flaps in a rat model [28,29]. However, a recent analysis of inflammatory biomarkers revealed that significant IR injury can occur with as little as two hours of ischemia [30].…”
Section: Plos Onecontrasting
confidence: 99%
“…However, a few mixed results were reported [ 18 , 19 ], including a case report with exacerbated lymphedema after VLNT [ 26 ]. Possible causes of suboptimal post-VLNT results include poor lymphangiogenesis and neo-lymphangiogenesis [ 2 , 27 ]; the quantity of LNs in the LN flap, which was shown to possess direct correlations with lymphatic drainage in animal models [ 28 ]; ischemic reperfusion injury during VLNT [ 29 , 30 , 31 ]; and pedicle complications (arterial or venous occlusion) during or after VLNT [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Critical ischemia time in muscle, skin, and other tissues have been extensively investigated in animal and human models [15,[18][19][20]. Relatively little is known about the effect of ischemia and ischemia-reperfusion injury on lymph nodes and lymphatic tissue [21,22]. Since we recently developed and characterized a transgenic rat which facilitates in situ real time visualization of lymphatic tissue (Prox1-EGFP), this has enabled us to precisely identify and isolate lymph nodes from surrounding tissue and analyze the cellular changes that occurred within lymph nodes [23].…”
Section: Introductionmentioning
confidence: 99%